Development of a Web-Based Sales Recording and Inventory Management Application for Optimizing Cutton and Co's Operations - Raharja, Annisa Amalia (SAINTIS Publishing, 2026)
Digital transformation has had a big effect on the retail and fashion industries by using information technology, especially web-based information systems. Cutton and Co, a local brand that makes clothes, bags, and wallets, still has problems with inventory management and sales recording because they do it all by hand using spreadsheets. This could lead to errors in data entry, delays in updating data, and problems with making reports. Lack of data integration between divisions and limited access to information also hinders the company's operational efficiency. The goal of this research is to design and build an integrated web-based information system that will help with real-time, accurate, and automatic stock management and transactions. The developed system is expected to enhance interdepartmental collaboration, accelerate business processes, and offer flexible data access. This system also supports production planning and sales performance analysis. The implementation of this system is expected to enhance operational efficiency and effectiveness, minimize recording errors, and facilitate accelerated, data-driven decision-making.